Adequação às normas de saúde e segurança do trabalho no manejo florestal comunitário na RESEX Verde para Sempre, Porto de Moz-PA - AZEVEDO, Michele (2021)
Extractive Reserves are areas where communities live that have their livelihoods mostly taken from the forest. Some form Associations or Co-operatives to work with Community Forest Stewardship, but these communities need to comply with both environmental and social standards, based on current legislation, such as those that ensure the health and safety of managers during their implementation. Forest management activities, thus allowing a legalized product, with insertion in attractive markets, when possible to obtain good management guarantee seals. With this bias, the objective of this paper is to analyze the adequacy of forest operations to the Occupational Health and Safety (OSH) standards in the sustainable forest management of the communities of Our Lady of Perpetual Help of the Arimum and Paraíso River, at RESEX Verde para Sempre, Porto de Moz-PA. Community data collection took place in two stages, the first was data collection through interviews with a semi-structured questionnaire with managers in the different functions performed within the community forest management enterprise and the second stage was through a form of observation of the characteristics of the workplace, including camping, transportation, roads and forest management area, observing the safety techniques taken to carry out field activities through verifiers. Of the 31 verifiers analyzed, the Arimum community totaled 9 nonconformities that are linked to infrastructure and safety procedures such as waste storage and outsourcing, respectively, while the Paradise community totaled 15 nonconformities related to safety in forest activities, infrastructure and safety procedures related to the use of risk-appropriate PPE, sanitary conditions and outsourcing of services.